Access to Care for VA Dialysis Patients During Superstorm Sandy - Lilia R. Lukowsky; Aram Dobalian; David S. Goldfarb; Kamyar Kalantar-Zadeh; Claudia Der-Martirosian (SAGE Publishing, 2019)
Introduction: This study examines the use of dialysis services by end-stage renal disease (ESRD) patients following the Superstorm Sandy-related, months-long closure of the New York campus of the US Department of Veterans Affairs (VA) New York Harbor VA Healthcare System (NYHHS, Manhattan VAMC). Methods: Outpatient visits, dialysis care, emergency department visits, and hospitalizations at VA and non-VA facilities for 47 Manhattan VAMC ESRD patients were examined 12 months pre- and post-Sandy using VA administrative and clinical data. Results: The Brooklyn campus of NYHHS, which is within ten miles of Manhattan VAMC, experienced the largest increase in the number of dialysis encounters after the closure. Dialysis encounters for VA patients also increased at non-VA facilities, rising on average, to 106 per month. For the James J Peters Bronx VAMC, the number of total dialysis encounters for Manhattan VAMC patients fluctuated between 39 and 43 per month, dropping to less than 30 after the Manhattan VAMC dialysis unit reopened. Conclusion: Manhattan VAMC ESRD patients used nearby alternate VA sites and non-VA clinics for their care during the closure of the Manhattan VAMC dialysis unit. The VA electronic health records played an important role in ensuring continuity of care for patients who exclusively used VAMC facilities post-Sandy because patient information was immediately accessible at other VA facilities. The events related to Superstorm Sandy highlight the need for dialysis providers to have a comprehensive disaster plan, including nearby alternate care sites that can increase service capacity when a dialysis facility is closed because of a disaster.